PENGARUH INFLASI, RETURN ON EQUITY, DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PT CIPUTRA DEVELOPMENT TBK PERIODE 2010-2023 - Ariyanti, Vici; Hadistia, Ananda (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of inflation on the stock return of PT Ciputra Development Tbk for the period 2010-2023, to determine the effect of return on equity on the stock return of PT Ciputra Development Tbk for the period 2010-2023, and to determine the effect of debt to equity ratio on the stock return of PT Ciputra Development Tbk for the period 2010-2023. The dependent variable is stock return, while the independent variables are inflation, return on equity, and debt to equity ratio. The method used is quantitative by analyzing the financial statements of PT Ciputra Development Tbk for the period 2010-2023.The partial test results show that inflation (t-count 0.779 ≤ t-table 1.7709), return on equity (t-count 1.710 < t-table 1.7709), and debt to equity ratio (t-count -0.425 < t-table 1.7709) do not significantly affect the stock return. The simultaneous test results indicate that inflation, return on equity, and debt to equity ratio collectively do not have a significant effect on stock return (F-count 2.001 < F-table 3.98). Thus, it is concluded that inflation, return on equity, and debt to equity ratio do not have a significant effect on the stock return of PT Ciputra Development Tbk for the period 2010-2023.